2022
DOI: 10.1007/s10238-022-00944-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving the malignancy prediction of breast cancer based on the integration of radiomics features from dual-view mammography and clinical parameters

Abstract: Purpose We developed a radiomics strategy that incorporating radiomics features extracted from dual-view mammograms and clinical parameters for identifying benign and malignant breast lesions, and validated whether the radiomics assessment can improve the accurate diagnosis of breast cancer.Methods A total of 380 patients with 621 breast lesions utilizing mammograms on craniocaudal (CC) and mediolateral oblique (MLO) views were randomly allocated into the training (n=486) and testing (n=135) sets in this retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…An intriguing study [36] highlights the importance of integrating dual-view radiomics with clinical characteristics in the context of breast cancer, demonstrating superior performance in malignancy evaluation. This is consistent with our methodology, in which the combination of radiomic and clinical variables produced increased discriminatory power, highlighting the need of a thorough approach in the prediction modeling of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing study [36] highlights the importance of integrating dual-view radiomics with clinical characteristics in the context of breast cancer, demonstrating superior performance in malignancy evaluation. This is consistent with our methodology, in which the combination of radiomic and clinical variables produced increased discriminatory power, highlighting the need of a thorough approach in the prediction modeling of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used in clinical research in tumors diagnosing, and curative effects predicting 24–27 . Radiomics aims to quantitatively extract features from diagnostic images and capture the nature of tissues and lesions, as well as to assess the tissue heterogeneity of a patient's tumor 28 . Biopsy captures heterogeneity in a small subset of tumors, while radiomics captures heterogeneity over the entire tumor volume.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Radiomics aims to quantitatively extract features from diagnostic images and capture the nature of tissues and lesions, as well as to assess the tissue heterogeneity of a patient's tumor. 28 Biopsy captures heterogeneity in a small subset of tumors, while radiomics captures heterogeneity over the entire tumor volume. Radiomics profiles have been shown to predict response to NACT in patients with CSCC, allowing clinicians to identify patients who may benefit from NACT.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics has been used in various modalities in the field of breast cancer [28]. In recent years, a number of studies, particularly those on mammography [29], have reported its usefulness not only for predicting whether a tumor is benign or malignant [30,31], but also its molecular subtypes [32,33], risk of recurrence [34], and prognosis [35]. Thus, a lot of information can be obtained from the radiomics features of mammography images; therefore, the risk of developing breast cancer can also be calculated, leading to individually optimized breast cancer screening methods [36].…”
Section: Introductionmentioning
confidence: 99%